2021
DOI: 10.1111/jocn.15987
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of workplace violence among nurses in the South‐East Asian and Western Pacific Regions: a systematic review and meta‐analysis

Abstract: Background Workplace violence (WPV) includes verbal abuse, physical violence, bullying or mobbing, assault and sexual harassment. The area has been well researched in the developed and high‐income countries among nurses and healthcare professionals, but in the case of the low and upper‐middle‐income countries, there remains a paucity of comprehensive data on the prevalence of WPV and its contributing factors. Aims To estimate the prevalence and determinants of WPV among nurses working in the South‐East Asian R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
46
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 68 publications
3
46
1
Order By: Relevance
“…Workplace violence or aggression is not a new phenomenon but a serious and growing problem that can be found in virtually all occupations [ 1 ]. And workplace violence is not a marginal phenomenon but rather an everyday event that is frequently observed and highly prevalent in social services and particularly in health care settings and among nurses [ 2 5 ]. And although workplace violence against health care workers is increasingly recognized and addressed in health (services) research, in public, practice and politics it always was and still is strongly underreported and largely ignored or tolerated [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Workplace violence or aggression is not a new phenomenon but a serious and growing problem that can be found in virtually all occupations [ 1 ]. And workplace violence is not a marginal phenomenon but rather an everyday event that is frequently observed and highly prevalent in social services and particularly in health care settings and among nurses [ 2 5 ]. And although workplace violence against health care workers is increasingly recognized and addressed in health (services) research, in public, practice and politics it always was and still is strongly underreported and largely ignored or tolerated [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Workplace violence against health care workers seems to be most common in the forms of verbal abuse and sexual harassment and particularly widespread in North American and Asian countries [ 3 , 4 , 6 , 15 , 16 ]. According to several systematic reviews up to two thirds of the nurses and other health professionals are exposed to violence at the workplace within a year, depending on the profession, setting (or context), country or study [ 3 5 , 15 , 17 , 18 ]. Health care workers are particularly affected from workplace violence and regularly confronted with aggression from patients or their relatives mainly because they are in frequent or even daily contact with people in distress and despair and/or with mental health problems [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Workplace violence against healthcare providers is on the rise (Gignon et al 2014;Yi et al 2020), while nurses usually have the most contact with patients and face the highest risk of violent attack, such as physical and verbal violence (Gomaa et al 2015). Nurses are at risk for direct trauma exposure in their daily work consequent to workplace violence, abuse, and workplace accidents (Okoli et al 2021;Varghese et al 2021). Studies have confirmed that nursing professionals' trauma exposure may reduce their work quality by increasing their vulnerability to stress, resulting in higher than normal incidences of work-related emotional distress, fatigue, burnout, secondary traumatic stress (STS), and posttraumatic stress disorder (PTSD) (Beck, 2011;Yi et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…While this analysis focused on violence perpetrated by patients and visitors, studies from across world regions document co-workers and supervisors as perpetrators of WPV as well. 3 , 4 …”
mentioning
confidence: 99%